Stimulated Brillouin scatter and stimulated ion Bernstein scatter during electron gyroharmonic heating experiments. Issue 5 (17th October 2013) - Fu, H.; Scales, W. A.; Bernhardt, P. A.; Samimi, A.; Mahmoudian, A.; Briczinski, S. J.; McCarrick, M. J.
<x xml:space="preserve">Abstract</x> [1] Results of secondary radiation, Stimulated Electromagnetic Emission (SEE), produced during ionospheric modification experiments using ground‐based high‐power radio waves are reported. These results obtained at the High Frequency Active Auroral Research Program (HAARP) facility specifically considered the generation of Magnetized Stimulated Brillouin Scatter (MSBS) and Stimulated Ion Bernstein Scatter (SIBS) lines in the SEE spectrum when the transmitter frequency is near harmonics of the electron gyrofrequency. The heater antenna beam angle effect was investigated on MSBS in detail and shows a new spectral line postulated to be generated near the upper hybrid resonance region due to ion acoustic wave interaction. Frequency sweeping experiments near the electron gyroharmonics show for the first time the transition from MSBS to SIBS lines as the heater pump frequency approaches the gyroharmonic. Significantly far from the gyroharmonic, MSBS lines dominate, while close to the gyroharmonic, SIBS lines strengthen while MSBS lines weaken. New possibilities for diagnostic information are discussed in light of these new observations.